Environmental impacts of Kuala Lumpur International Airport 2 (KLIA2) during its construction stage - Syazwani binti Sahrir (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2014)
Transportation is an essential sector of the economy, contributing more than 5 percent to the annual Gross Domestic product of the nation. However, the growth in transportation sector creates environmental issue such as air pollution. The thesis assessed the environmental impacts of airport infrastructure upgrading and the construction of Kuala Lumpur International Airport 2 (KLIA2), the second budget airline airport to support the current international airport in Malaysia. This development of new airport has created significant adverse effects ranging from physical effects to the environment, land use compatibility, to a direct impact on the health of the surrounding communities. The study tested and examined environmental impacts namely particulate matter (PM) and noise level caused by the airport development during construction stage. Some of the crucial environmental concerns in airport development are health levels, community severance, noise levels, local air quality and sustainability, as well as the loss of habitat and wildlife in the area. In addition, companionable and synchronized land uses are crucial to the discussion of the airport, regional transportation linkages and regional planning. It is clear that the changing role of airport development will involve new airport construction, in terms of its function as a transportation hub, as well as a retail and commercial area. Various airborne particulate matter samplers (Cyclone Sampler and & 7 Hole Sampler) and sound level meter (SLM) used to record both noise and particulate matter levels. The research identified five sampling locations within the study area and also the airport's surrounding areas. The sampling locations were selected based on the intensity of the development within the sites and the severity of land use changes. Variables such as construction area size, development intensity, particulate matters and sound levels have been examined against the infrastructure upgrading of the airport over time and space. These variables of particulate matter and noise have been found to be significant outcomes of airport development. Instead, this thesis concluded that increased intensity of construction activities and land use changes had direct relationships with noise and particulate matter levels. It is hoped that the findings of the study would assist in providing better insight into the intangible costs incurred and benefits derived from an airport construction on land use changes. Most importantly, new airport planning and consultation measures are needed to mitigate risks from airport developments in seeking a common platform of fairness, certainty and transparency so that the opportunity to recognize broader planning consequences and governance questions of airports in their spatial settings is not lost.